Experiences of family members of people on hemodialysis during the novel corona virus pandemic (COVID-19) (Research, Society and Development, 2020)
This is a scientific essay aiming to reflect the experiences of family caregivers of people with chronic kidney disease undergoing hemodialysis during the Novel Corona Virus Pandemic (COVID-19). Its main argument is that the imperative need for keeping the person in hemodialysis sessions in the period when health agencies recommend social isolation has triggered and intensified negative feelings in the family caregivers. The foundations for reflection include: health condition vulnerability of the family member who performs hemodialysis, frustration before the impossibility of keeping him/her in social isolation, apprehension and fear of his/her own exposure to the risk of getting the virus and transmit it to the person under his/her care, or even falling ill and die leaving the sick person without family support. The pandemic is considered to have challenged people to be creative and to reframe their spaces and relationships to overcome fear, pessimistic or alarmist thoughts. Thus, personal self-achievement encouragement, discovery of pleasant activities, practice of hobbies, conversations with and listening to family members and friends even if it is through the virtual network, sharing of emotions and feelings, spiritual and religious practice, and dialysis unit formal support with institutional reorganization, expansion of care and psychological support measures, can serve as a basis for family caregivers and sick people undergoing hemodialysis to overcome this adverse period.